STRATEGI PEMASARAN PENDIDIKAN DALAM MENINGKATKAN CITRA LEMBAGA SEKOLAH: STRATEGI PEMASARAN PENDIDIKAN DALAM MENINGKATKAN CITRA LEMBAGA SEKOLAH - Riyanto, Riyanto; Masithoh Kharisma (STAI KH. Muhammad Ali Shodiq, 2024)
Education marketing strategies have an important role in building and improving the image of education and school institutions. In this era of highly competitive competition, educational institutions are required to carry out effective strategies. This research aims to determine effective marketing strategies in building a positive image of schools, both through direct and digital promotions. The approach used includes literature analysis and literature study. The research results show that the key elements for success include school branding, use of social media, community involvement, improving service quality, and testimonials from students and alumni. Apart from that, collaboration with parents and other institutions has also been proven to strengthen the school's image. Implementing digital-based marketing strategies, such as creating creative and interactive content, has a significant impact in reaching a wider audience. In conclusion, a well-planned education marketing strategy can increase the attractiveness of a school while building public trust in the quality of education offered. Keywords: School Marketing Strategy, Marketing Education Services, School Image.